Bank-affiliated institutional investors and IPO syndicates formation - Pratobevera, Giuseppe (Journal of Corporate Finance, 2024)
By using institutional trading data in a sample of US IPOs, I provide evidence that IPO syndicate banks use their affiliated institutional investors to build a relationship with IPO lead underwriters and boost their underwriting business. First, I show that investment managers provide unprofitable price support in the aftermarket of IPOs in which their parent banks are non-lead syndicate members. This costly support is concentrated in cold IPOs and IPOs net sold by independent institutions. Second, I show that lead underwriters are more likely to select in the IPO syndicate the banks whose affiliated institutional investors support IPO prices. I discuss and document evidence of the incentives of underwriters and affiliated institutions that make price support emerge in equilibrium.